Comparing Internal and External Severe Maternal Morbidity (SMM) Review in Illinois [06L]. (May 2020) - Geller, Stacie; Garland, Caitlin; Horne, Ashley; Locher, Stephen
Abstract : INTRODUCTION: A majority of states have implemented maternal mortality review committees, but Illinois is the only state to also implement facility-level, multidisciplinary review of SMM at all obstetric hospitals as recommended by the Centers for Disease Control and Prevention and American College of Obstetricians and Gynecologists. METHODS: Facility-level multidisciplinary SMM review was implemented in all perinatal networks in 2017 using a modified 2-factor scoring system recommended by CDC/ACOG (ICU admission and >4 units of packed red blood cells). A standing external, multidisciplinary SMM review committee was also established to review a subset of reviewed cases to improve the hospital review process and to compare external committee decisions to the internal review. RESULTS: The external committee found 34% of SMMs were potentially preventable compared to 16% across internal review. In external review, the most common factors contributing to SMM was medical decision making, however internal review found pre-existing conditions and pregnancy complications as leading preventable factors. The external committee found more provider (63% vs 16%) and system (41% vs 16%) opportunities to alter SMM than the internal committees (patient factors). CONCLUSION: This study is the first to present findings on statewide implementation of SMM review both within hospital and by external committee and compare parallel facility-level and state-level review. External review shows more preventability and more provider and system opportunities to prevent SMM compared to internal review. External review by a multidisciplinary committee provided more opportunities to identify strategies to alter outcomes, however both offer opportunities for quality improvement and population-based findings.